Excessive Metals’ Influence Over Soil Characteristics and Microbial Restoration - Abdullah, Shaikh; Saddam, Shaikh; Roonjha, Muhammad Afzal; Shaikh, Ghulam Yasin; Metlo, Wazir Ali; Mahmood, Tariq; Lashari, Saima; Shaheen, Nadia; Muhammad Sufyan; Muhammad Mansoor (Indus Journal of Bioscience Research, 2024)
Such elements having atomic density more than 4g/cm3 or 5 times or more than water are heavy metals i.e. Nical (Ni), silver (Ag), cobalt (Co), iron (Fe), manganese (Mn), lead (Pb), arsenic (As) and cadmium (Cd). In these some are essential i.e. iron (Fe), zinc (Zn), copper (Cu), manganese (Mn), molybdenum (Mo) and Nical (Ni). Rapid increments in industry, agriculture, urbanization produce non-degradable toxic material i.e. heavy metals. Heavy metals are also produced by natural resources but higher values reflect anthropogenic accumulation. Soil is a one of the valuable, essential, non-regenerative resource. Many soil properties i.e. pH, organic contents, ion exchange capacity, texture, microbial growth, microbial density or metabolic processes are deteriorated by the heavy metals accumulation. Heavy metals are non-degradable part of soil environment. Soil remediation is necessary due to high productive pressure with food security concerns. Different physico-chemical and biological practices are in practice to remediate soil environment. Mainly use of amendments (liming material, organic contents and adequate fertilizer rate) and plants (phytoremediation and phytodegration) are most economic cost effective and environmentally well sounded technique for cleanup of soil environment. Amendments help to reclaim the soil physico-chemical properties, microbial community establishment and bond different heavy metals to reduce their mobility. Prevention in the entry of heavy metals in food chain is major goal of phytoremediation. Physical with genetic engineering approaches must be practiced to make new genetically controlled plants used in future prospect to remediate the soil.